PENJABARAN STANDAR INTERNASIONAL TRIMS DAN OECD DALAM KETENTUAN HUKUM PENANAMAN MODAL INDONESIA - Ni Ketut Supasti Dharmawan; Putu Tuni Caka Bawa Landra; Putu Aras Samsithawrati (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
As a member of the WTO-TRIMs Agreement basically Indonesia has stipulated the NationalTreatment Principle to the legal provisions relating to investment activities. However, theIndonesian investment Law (Law No. 25 of 2007) still remains that the regulation of NationalTreatment with regard to national interests. In order to the difficulties may exist in domesticlevel such as the social, economic as well as values may be different in some member countries,the WTO-TRIMs provide exceptions for the member with notify mandatory requirement tothe Board of TRIMs. Relating to investment activities other International standards alsorelevant to study is the GCG principles developed by the OECD. Although Indonesia is notOECD member countries, the GCG principles adopted in various Indonesian laws relatedto investment activities doe to it relevant and harmony to the economic, social as well ascommunity values in order to develop capital investment.